Jokowi Administration's Maritime Axis Development Policy - Sitanggang, Sondang Novita (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2023)
Jokowi focus their governments to make Indonesia as the pivot of the maritime world greeted well considering Indonesia is a country that is two-thirds of the area consists of resource-rich waters and kelautan. Indonesia consists of 92 outer islands and 31 of them inhabited. As stated by Sukarno, in one of his speeches, Indonesia will become a strong nation if it has the ability or marine waters were strong, maritime shaft also have the same goal. This thesis discusses discusses the strategies and policies that have been planned by the government to make Indonesia as a maritime shaft. Jokowi as the pivot of the world's maritime evidenced by forming ministries coordinate their work and concentrated in maritime terms. Creating a strong quality of human resources in the field of maritime pariisata both capabilities in innovation and adaptation in the face of change, work culture and concepts to be implemented.